Development of a Village Citizen Reporting Website for Smart Village Village Public Services - Monika Dian Pertiwi, Kharisma; Muhajir, Daud; Ananda, Dahliar; Santik, Tita Arum Shela; Pratama, Moch. Andi Divangga; Adityo, Kahil Akbar Bayu; Jungjungan, Fadhlan Syahran (Abdi Masyarakat, 2024)
The development of technology that has been supported by the government makes it easier for citizens to get information, and can influence society to get information and participate in public policy. The development of technology carried out by the government starts from public services on digital platforms, such as websites or village applications. Smart Village initiated by Telkom University Surabaya innovates by providing a website to help citizens with easy complaints to providing a space for community aspirations that can be accessed anywhere and anytime by the people of Panjunan Village. The Public Complaints Website has 31 features for citizens, officers and admins, these features have been tested functionally, and have been tested on several users, in the test no functional errors were found in the sense that the system is ready to use.